ORGANIZING LESSONS OF WRESTLING IN SCHOOLS - Abdirakhmon Rakhmatovich Beknazarov; Zukhra Mirsoatovna Shermatova (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses how to organize wrestling lessons in schools today, the types of lessons, their tasks, and the stages of lesson organization. In addition, it discusses the features a teacher should pay attention to when organizing wrestling lessons, and ways to achieve more effective results no matter how the lessons are organized.